Numerical modeling and simulations of active direct methanol fuel cell (DMFC) systems under various ambient temperatures and operating conditions. (19th January 2017) - Lee, Junhee; Lee, Suwon; Han, Donghee; Gwak, Geonhui; Ju, Hyunchul
Abstract: Direct methanol fuel cells (DMFCs) are potential candidates for portable backup power generation and auxiliary power units owing to their advantageous features, such as ease of fuel storage and delivery. Optimizing each component of a DMFC system is critical to improving the overall system performance and power density. This paper presents an active DMFC system model, in which a one-dimensional DMFC stack model is combined with major system components, including fuel and water tanks, liquid–gas separator, heat exchangers, pumps, and blowers. The model is implemented using a commercial flow-sheet simulator, ASPEN-HYSYS, and then applied to an active DMFC system to analyze the effects of the DMFC operating parameters and heat management. Special emphasis is placed on establishing active control strategies for the DMFC stack temperature, methanol crossover rate, and water recovery by optimizing the system components and operating conditions. Overall, this study helps identify innovative active DMFC system designs and configurations. Highlights: The numerical model of active direct methanol fuel cell (DMFC) system is developed. A 1-D DMFC stack model and 0-D DMFC system model are combined. 0.6 M is an optimal methanol feed concentration for the highest stack performance. The simulation reveals the impacts of ambient and anode inlet temperature.